A Case of Decannulating Incompetent Great Saphenous Vein Filling Cyanoacrylate because of Type IV Hypersensitivity - Suzuki, Hiroyuki; Nakayama, Mayuko; Wada, Hideichi (Japanese Journal of Vascular Surgery, 2022)
Cyanoacrylate closure for the treatment of incompetent great saphenous vein have accepted as insurance coverage in Japan. This treatment is non-thermal and non-tumescent technique. However, there are some cases develop postoperative complication. We describe allergic-like reaction caused by cyanoacrylate closure for the treatment of incompetent great saphenous vein. A 79-years-old woman had this treatment, developed swelling of diseased side leg seven days after the treatment. We suspected that there was some kind of allergic reaction. This case got a DLST, and the result was positive. We diagnosed this case as type IV hypersensitivity, administered drugs. But, the symptoms were not improved. As a result, we decannulate left saphenous vein filling CA.